Procedural 3D modeling using geometry nodes in blender : discover the professional usage of geometry nodes and develop a creative approach to a node-based workflow /: discover the professional usage of geometry nodes and develop a creative approach to a node-based workflow. (2023) - Lens, Siemen
No abstract available